Clinical Course and Results of Anti-VEGF Therapy of Retinopathy of Prematurity - L. A. Katargina (Oftalʹmologiâ, 2021)
The clinical course of active retinopathy after anti-VEGF therapy, the possibility and timing of recurrence of the disease, anatomical and functional outcomes of treatment are widely discussed in the press, not fully studied and relevant.Purpose: to study the clinical course of active retinopathy of prematurity after anti-VEGF therapy and clinical and functional outcomes.Patients and Methods. Children with active retinopathy of prematurity, who turned to the Helmgoltz National Medical Research Centre of Eye Diseases after anti-VEGF therapy, examined by indirect binocular ophthalmoscopy and digital retinal camera (RetcamShuttle). Children were monitored from 1.5 to 6 years (average 2.94 ± 1.47). All children underwent routine examination, 4 children older than 3 years underwent optical coherence tomography.Results. In all cases, after anti-VEGF therapy, there was a decrease in vascular activity and continued vascularization of the retina. Recurrence of the disease requiring additional treatment, were detected in 11 (42.3 %) eyes within 6–22 weeks (in average 13.33 ± 5.57) after intravitreal anti-VEGF therapy. Laser coagulation of the retina was carried out in 4 children (7 eyes) and repeated administration of anti-VEGF drug — 2 children (4 eyes), which led to regression of the disease. In the long-term period, all 13 (100 %) children had successful outcomes.Conclusion. Anti-VEGF therapy is effective in plus-zone 1 disease and posterior aggressive retinopathy of prematurity. Its advantages include the ability to treat retinopathy in zone 1 posterior, the absence of “blockade” of the peripheral retina with the possibility of continued growth of blood vessels to the periphery, lower frequency and severity of myopia. The disadvantages include the possibility of recurrence of the disease, which requires long-term regular monitoring.